The School Experiences of Siblings of Children With Chronic Illness: Australian Parents' Perceptions. (2nd April 2018) - Gan, Lucy L.; Lum, Alistair; Wakefield, Claire E.; Donnan, Barbara M.; Marshall, Glenn M.; Burns, Mary A.; Jaffe, Adam; Leach, Steven; Lemberg, Daniel A.; Fardell, Joanna E.
Abstract : Children with chronic illness often experience difficulties at school, yet little is known about the impact of the child's illness on siblings' school experiences. This study investigated parents' perceptions of siblings' school experiences and school support. We conducted semi-structured telephone interviews with 27 parents of children with a chronic illness who had a sibling or siblings (4–25 years), representing the experiences of 31 siblings. Interviews were audio-recorded, transcribed, and analysed using content analysis. Parents believed that 14 of 31 (45.2%) siblings had school difficulties related to the ill child, such as increased anxiety or stress at school, lack of attention from teachers, and changes in behaviour as a result of increased carer responsibilities. Parents identified increased absenteeism due to the ill child's hospitalisation and the impact of parent absences on sibling school functioning. Parents described general and psychological support from the school, and the importance of monitoring the sibling at school and focusing on their unique needs. Overall, our findings suggest the need for a school-based sibling support model that combines psycho-education for siblings and school personnel, individualised sibling psychological support, and shared school and parent responsibility in normalising the sibling experience and providing consistent support.